Body posture aftereffects—does viewing slouched bodies change people’s perception of normal posture? - Eva Tzschaschel; Ian D. Stephen; Kevin Brooks (Royal Society Open Science)
People lead increasingly sedentary lifestyles and spend extended periods sitting in slouched and head-forward positions, which can lead to health issues. People are so accustomed to seeing slouched posture that they may perceive it as normal and fail to notice their own slouched posture. We aim to investigate this possibility using the visual adaptation paradigm, which has provided insights into the perception of body size and shape in the context of exposure to thin bodies in the media. The experiment was conducted in three phases. First, participants established the posture they perceived as normal by manipulating body stimuli shown in profile view. In the second phase, the adaptation phase, participants viewed bodies with extremely upright or slouched postures before establishing their perceived normal posture again in the third phase. Perceived normal posture differed significantly before versus after adaptation, demonstrating a visual aftereffect. However, this only applied if test and adaptation bodies were presented in the same orientation, suggesting that our representation of posture is retina-centred rather than object-centred. This result reduces the likelihood that visual adaptation influences the increase in slouched posture in the population. These results contribute to understanding visual influences on people’s perception of body posture.